Effects of taxes on youth self-employment and income - Johan Egebark (Research Institute of Industrial Economics (IFN), 2016)
I study the link between taxes and youth self-employment. I make use of a Swedish reform, implemented in 2007-09, which suddenly made the payroll tax and the self-employment tax vary by age. The results suggest that youth self-employment is insensitive to tax reductions, both in the short run and in the somewhat longer run. I also study the effect of the tax reductions on income. For those that are defined as self-employed, I find positive effects on income from self-employment, and negative effects on income from wage employment. This finding suggests that the lower taxes caused the self-employed to reallocate time from employment to self-employment.
Keywords: H25; H32; J23; J38; J68; 330; Youth unemployment; Self-employment tax; Tax subsidy; Self-employment